The role of nongovernmental organizations in China's climate change governance. (8th August 2017) - Liu, Lei; Wang, Pu; Wu, Tong
Abstract : Nongovernmental organizations (NGOs) have been a key player in international climate negotiations. In addition to being UNFCCC observers at the international level, the role of NGOs in domestic climate change governance has differed across countries due to varying political, legislative, and even cultural contexts. As the largest CO2 emitter in the world, China is engaged in the challenging process of low‐carbon development, which may not be achievable through exclusive reliance on top–down management and voluntary actions by the private sector. The participation of NGOs as a civil society actor is important. However, current understanding about the role of NGOs in China's climate change governance has been under‐studied. Climate change is still a relatively new topic for China's NGOs, and it has been difficult to differentiate the involvement of NGOs in climate change issues from their involvement in environmental issues more generally. Overall, the role NGOs play in China's climate change governance has had four main features: government partnership with restricted political space, organization development with inadequate professional capacity, strong international financial reliance but with growing domestic support, and public advocacy with low social recognition. WIREs Clim Change 2017, 8:e483. doi: 10.1002/wcc.483 This article is categorized under: Policy and Governance > Private Governance of Climate Change Abstract : The salient characteristics of the role of nongovernmental organizations (NGOs) in China's climate change governance are: partnership with government within a delimited political space, organizational development with inadequate professional capacity, reliance on international funding but with rising domestic support, and low recognition in society at large.